Pengembangan wisata religi petilasan Pangeran Benowo di Kecamatan Bener Kabupaten Purworejo - Junaidi Safitri; Dyah Hendrawati (UII, 2020)
The existence of religious sites is currently very popular among the community, so that the existence of this religious site is not only a site to be visited as a destination for takziyah but also along with the development of the existing religious sites can provide other economic values, namely as a medium for preaching and trading.One such religious site is located in Benowo Village, Bener District, Purworejo Regency. namely the Prince Benowo site which became the forerunner to the existence of Benowo Village in Purworejo Regency. Prince Benowo is the son of the king of the Pajang kingdom named sultan Hadiwijaya or better known as Jaka Tingkir, where during the Dutch colonial period around 1600 AD Prince Benowo and his followers stepped aside or took refuge somewhere on the way from the Pajang kingdom to the Mataram kingdom and stopped at Menoreh Mountains, to be precise on a hill called Batur, which is currently known to the general public as Benowo Village.Prince Benowo's petilasan is currently being used as religious tourism which can be a special attraction for tourists to visit Benowo village. Tourists can see the historical value of the existence of Prince Benowo's petilasan, including the existence of the sendang used by the followers of Prince Benowo for drinking and cleaning, as well as items used by Prince Benowo's entourage, including ceramic plates, stone bowls, umbrellas, and etc.The existence of special religious interest tourism has made the managers of the Benowo tourism village start to improve by optimizing the existing tourism potential, both natural, cultural and artistic tourism to be able to attract more tourists to visit Benowo tourism village. The weaknesses of the development of this religious tourism village in Benwo Village are 1) There is no development plan for the development of existing religious tourism potential, and 2) Prince Benowo Religious Tourism has not been managed properlyBased on the above problems, the service and partners will solve the above problems through planning training activities for the development of religious tourism, Prince Benowo, and 2) Assistance in the management of religious tourism through strengthening human resources. So that the output target of this service activity is 1). The creation of religious tourism development in Benowo village, 2) The creation of religious tourism governance